Perlindungan Hukum terhadap Perawat dalam pelimpahan Kewenangan pada Tindakan Kedokteran - Sri Yani; Sabir Alwy; Mappeaty Nyorong (Politeknik Kesehatan Kemenkes Mamuju, 2020)
Delegation of authority is the process of transferring tasks to other legitimate or legitimate people in carrying out various activities aimed at achieving certain goals. In the implementation of the delegation of the authority of medical action from doctors to nurses must be carried out in writing and the mechanism for implementing the delegation of authority must be clear. This study aims to determine the legal protection of nurses in the implementation of the delegation of authority on medical actions and the mechanism of implementing the delegation of doctor's authority to nurses. The research method used is empirical legal research by interviewing and filling out questionnaires as primary data and the legal approach and conceptual approach. Data is analyzed qualitatively. The results showed that most of the knowledge of medical personnel (83.3%) and nurses (88.9%) regarding the delegation of authority and legal protection to medical actions was still lacking. This is because medical personnel and nurses do not know about legislation related to the delegation of authority from medical personnel to nurses. The West Sulawesi Provincial General Hospital and the Mitra Manakarra Mamuju Hospital are still using doctor's instructions as a form of delegation and consider the implementation of delegation of authority from doctors to nurses as a routine activity that is usually done. The delegation implementation mechanism in the form of a special format for delegation, hospital leadership decree and standard delegation operational procedures has never been made. This will affect the implementation of the delegation of authority of medical personnel to nurses. As a result, medical personnel and nurses have not been guaranteed maximum legal protection in hospitals. The conclusion states that the statutory regulations regarding the delegation of authority from medical personnel to nurses and the mechanism of delegation have not been optimally implemented